Karakteristik Mekanik Komposit Serbuk Kayu Dengan Polymer Sintetis (Polyester Dan Epoxy) - Muttakin, Amrullah; Kencanawati, C.I.P.K; Astawa, Ketut (Teknik Desain Mekanika, 2022)
Abstract The use of wood as basic materials to meet the increasing needs of the community has resulted in more wood waste being produced. Teak wood waste in form of powder can be reused as a basic material for making composites to increase the value of the powder. This study aims to determine the mechanical characteristics of wood powder composites with synthetic polymers (polyester and epoxy). Wood sawdust composites used a mass fraction variation of 5% : 95%, 10% : 90%, 15% : 85% in the type of resin, namely polyester and epoxy. The tests carried out are impact tests referring to the ASTM D256 standards and water absorption tests referring to the ASTM D570-98 standards. The results of the impact test of the wood powder composite specimen with an epoxy resin matrix at a mass fraction of 15% : 85% had the greatest impact strength with a value of 0,0112 Nm/mm2. The results of water absorption test on wood powder composite specimens with an epoxy resin matrix obtained the lowest absorption value with a value of 0,67% at a mass fraction of 15% : 85%. Keywords : teak powder, composite, impact test, water absorption test, polyester, epoxy, synthetic polymer